Zechariah and his prophecies considered in relation to modern criticism, with a critical and grammatical commentary and new translation. - Wright, Charles Henry Hamlton (London, UK Hodder and Stoughton, 1879)
"Eight lectures delivered before the University of Oxford in the year 1878, on the foundation of the late Rev. John Bampton, M.A., Canon of Salisbury." Includes bibliographical references and index.
1980 reprint by Klock and Klock Christian Publishers, Minneapolis, MN.
Keywords: Bible. O.T. Zechariah. Apocalyptic passages -- commentaries